Attitudes toward and exposure to gender discrimination in work life by pulmonologists and thoracic surgeons: a questionnaire-based survey among Turkish thoracic society members - Ocakli, Birsen; Yorgancioglu, Arzu; Gungor, Sinem; Topcu, Fusun; Senol, Yesim Yigiter; Goktas, Basak; Kokturk, Nurdan; Tuncay, Eylem; Gundogus, Baran; Altinoz, Hilal; Yasin, Yesim; Ozmen, Ipek; et al. (Frontiers in Medicine, 2024)
Background: This study aimed to evaluate attitudes toward and exposure to gender discrimination in work life by chest diseases specialists and thoracic surgeons Methods: A total of 275 members of Turkish Thoracic Society (TTS) were included on a voluntary basis in this online cross-sectional questionnaire-survey using an internal member-only social media platform of TTS. The questionnaire form elicited items on sociodemographic characteristics, occupational characteristics and gender discrimination in work life (general opinions, attitudes and exposure). Results: Female doctors (vs. males) were less likely to be a thoracic surgeon (13.8% vs. 34.5%, p<0.05) and a professor of thoracic surgery (0.0% vs. 26.7% vs p<0.05), and more likely to consider housework as a considerable burden (89.8 vs. 73.6%, p=0.02) and the significant role of discriminatory, negative and dissuasive attitudes of male physicians in their career choice (67.6 vs. 35.6%, p=0.039). Male doctors were more likely to considered that men are more successful in specialties that require active physical strength (65.5 vs. 27.7%, p=0.005) and those with very long working hours and heavy shifts (57.5 vs. 39.4%, p=0.001). Female thoracic surgeons were more likely than males to consider that specialties with very long working hours and heavy shifts are more suitable for men (26.9 vs. 6.0%, p=0.027) and men are given priority in academic career promotion (64.0 vs. 13.3%, p<0.001). Younger (vs. older) females reported higher rate of exposure to gender discrimination (p=0.041) and considerable impact of social roles on the specialty (p=0.007), while female doctors working as a resident (33.8%) and a specialist (50.05%) indicated higher rate of exposure to gender discrimination during their career (p=0.024). Conclusion: In conclusion, our findings revealed that exposure to gender discrimination in work life was more commonly expressed by female members of TTS, particularly in terms of burden of social roles, career advancement options and leadership positions, along with significant role of discriminatory, negative and dissuasive attitudes of male physicians in their career choice. Accordingly, women remain underrepresented in thoracic surgery, particularly in the academic rank of full professor and in leadership positions with inability to promote after a definite step in their careers.